THE IMPLEMENTATION OF PROPORTIONALITY PRINCIPLE IN COMMERCIAL CONTRACTS OF FRANCHISE SECTOR - Amelia, Eva Ayu; Sholehuddin, Dr. M.; Rijadi, Prof. Dr. Prasetijo (Acitya Wisesa: Journal of Multidisciplinary Research, 2024)
The principle of proportionality is an integral legal principle in ensuring the balance of rights and obligations in commercial agreements, including franchises. This research aims to examine the function and purpose of the principle of proportionality in a franchise contract and analyze its implementation in the process of forming and performing the contract. The research method used is normative juridical with a legislative approach and analysis of literature related to the principle of proportionality in contract law. The results show that the principle of proportionality has a significant role in preventing imbalances in rights and obligations between franchisors and franchisees. The implementation of this principle in franchise contracts also contributes to creating legal certainty and reducing the potential for disputes due to imbalances in the agreement. Therefore, the implementation of the principle of proportionality in franchise contracts not only protects the rights of both parties, but also ensures fairness in the implementation of commercial contracts in the franchise sector.